A Novel Method to Quantify Self-Healing Capabilities of Fiber-Reinforced Polymers - Scazzoli, Cecilia; Trigueira, Robin; Cohades, Amaël; Michaud, Véronique (Frontiers in Materials, 2022)
The present work investigates a novel and practical method to evaluate the healing efficiency of carbon-reinforced polymer composites. The method should be representative of damage occurring during the lifetime of a composite part, should tend to damage the healable matrix mostly and yet be simple and cost-effective to set up. Thus, the capacity to recover low-velocity impact damage has been evaluated via three-point bending flexural tests. Carbon-reinforced composite laminates were produced using HealTech™ T300-TW200-42RW-1250, a commercial healable resin pre-impregnated Torayca T300 3K twill 2 × 2 fabric with an aerial weight of 200 g/m2. Fibers were oriented at ± 45° or at 0°–90°, and the laminates were impacted at different energy levels. Flexural properties of undamaged, damaged, and healed samples were compared, and the healing efficiency was calculated as the ratio of healed and undamaged ultimate flexural strength or modulus. Since matrix healing efficiency is the value to characterize, it was shown that ±45° laminates could be tested without major fiber damage and, thus, provide the best matrix healing efficiency results. Such a method proved to be 1) representative of early-stage damage of composite FRPs often occurring in the form of delamination or matrix microcracking, and 2) a fast and reliable characterization technique requiring the use of a limited amount of material.